The Motivation for Physical Activity at Night (A Case Study on Semarang Runners Community) - Saleh, Aga Eppino; Rahayu, Tandiyo; Soekardi, Soekardi (Journal of Physical Education and Sports, 2019)
In the era of modernization, the ever-increasing activities have left individuals with less time to rest and exercise and thus have impacted on their health. Busy work hours have forced people to use their night times to keep their bodies healthy. The purpose of this study is to analyze the motivations (physical, psychological, and social) of Semarang Runners Community members behind their night physical activities. The research design is a descriptive qualitative case study adopting purposive and snowball sampling techniques. Using the first seven informants as the data sources (1 the key and six other the main), the results showed the physical motivations are to lose weight and maintain health, the psychological motivations to channel hobbies and recreation and to relieve stress and the social motivation to add more friends. The study concludes physical motivations of losing weight and maintaining health to be the first motivations of becoming a member of the Semarang Runners community, which are followed by the psychological motivation on the second and the social motivation the last.